Improved survival with enasidenib versus standard of care in relapsed/refractory acute myeloid leukemia associated with IDH2 mutations using historical data and propensity score matching analysis - Stéphane deBotton; Joseph M. Brandwein; Andrew H. Wei; Arnaud Pigneux; Bruno Quesnel; Xavier Thomas; Ollivier Legrand; Christian Recher; Sylvain Chantepie; Mathilde Hunault‐Berger; Nicolas Boissel; Salem A. Nehme; et al. (Cancer Medicine, 2021)
Abstract Background The present study evaluated the relative survival benefits associated with enasidenib and current standard of care (SoC) therapies for patients with relapsed/refractory (R/R) acute myeloid leukemia (AML) and an isocitrate dehydrogenase 2 (IDH2) mutation who are ineligible for hematopoietic stem cell transplantation (HSCT). Methods Propensity score matching (PSM) analysis compared survival outcomes observed with enasidenib 100 mg daily in the phase I/II AG221‐C‐001 trial and SoC outcomes obtained from a real‐world chart review of patients in France. Results Before matching, enasidenib (n = 195) was associated with numerically improved overall survival (OS) relative to SoC (n = 80; hazard ratio [HR], 0.82; 95% confidence interval [CI], 0.61–1.11). After matching and adjusting for covariates (n = 78 per group), mortality risk was significantly lower with enasidenib than with SoC (HR, 0.67; 95% CI, 0.47–0.97). The median OS was 9.26 months for enasidenib (95% CI, 7.72–13.24) and 4.76 months for SoC (95% CI, 3.81–8.21). Results remained robust across all sensitivity analyses conducted. Conclusions PSM analyses indicate that enasidenib significantly prolongs survival relative to SoC among patients with R/R AML and an IDH2 mutation who are ineligible for HSCT. Future prospective studies are needed to validate these findings using other data sources and to assess the comparative efficacy of enasidenib for other treatment outcomes.